IncHI1 plasmids mediated the tet(X4) gene spread in Enterobacteriaceae in porcine - Ma, Jiangang; Wang, Juan; Yang, Hua; Su, Mengru; Li, Ruichao; Bai, Li; Feng, Jie; Huang, Yuting; Yang, Zengqi; Tang, Biao (Frontiers in Microbiology, 2023)
The tigecycline resistance gene tet(X4) was widespread in various bacteria. However, limited information about the plasmid harboring the tet(X4) gene spread among the different species is available. Here, we investigated the transmission mechanisms of the tet(X4) gene spread among bacteria in a pig farm. The tet(X4) positive Escherichia coli, Klebsiella pneumoniae, Enterobacter cloacae and Enterobacter hormaeche were identified in the same farm. The whole genome sequencing (WGS) analysis showed that the K. pneumoniae belonged to ST727 (n=11) and ST3830 (n=1), E. cloacae and E. hormaeche belonged to ST524 (n=1) and ST1862 (n=1). All tet(X4) genes were located on the IncHI1 plasmids that could be conjugatively transferred into the recipient E. coli C600 at 30°C. Moreover, a fusion plasmid was identified that the IncHI1 plasmid recombined with the IncN plasmid mediated by ISCR2 during the conjugation from strains B12L to C600 (pB12L-EC-1). The fusion plasmid also has been discovered in a K. pneumoniae (K1L) that could provide more opportunities to spread antimicrobial resistance genes. The tet(X4) plasmids in these bacteria are derived from the same plasmid with a similar structure. Moreover, all the IncHI1 plasmids harboring the tet(X4) gene in GenBank belonged to the pST17, the newly defined pMLST. The antimicrobial susceptibility testing was performed by broth microdilution method showing the transconjugants acquired the most antimicrobial resistance from the donor strains. Taken together, this report provides evidence that IncHI1/pST17 is an important carrier for the tet(X4) spread in Enterobacteriaceae species, and these transmission mechanisms may perform in the environment.